Analisis Pengaruh Permintaan E-Money, Jumlah Uang Beredar (M1), Produk Domestik Bruto (PDB) terhadap Velositas di Indonesia (April 2007 – Desember 2017) - Sari, Rysqi Puspita; Yunani , Ahmad (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
This journal investigates, analyzes, and understands the influence of the independent variables (e-money demand, M1, GDP) on the dependent variable (velocity) in Indonesia from April 2007 to December 2017. It also detects which independent variables have the most influence on performance velocity. The analytical tool used is multiple linear regression, t-test, and the F test. This study takes data from April 2007 to December 2017. The result proves that e-money demand is not too partial effect on velocity, but simultaneously still influential. While M1 and GDP are dominant and have a partial and simultaneous influence on speed.